OPTIMALISASI PELAYANAN PADA KELURAHAN KATIMBANG KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Safira, Alya; Herdayani Darsim, Sitti Khadijah (ADMIT: Jurnal Administrasi Terapan, 2024)
Optimal public service is reflected in sufficient resources to carry out and complete the assigned tasks. Important issues that often arise include uncertainty and the quality of service, which does not meet the level of public satisfaction in receiving public services. One such issue is that Katimbang Village has not yet established a service standard document. Clear and measurable service standards are crucial as a reference for employees in providing services, ensuring that satisfactory results are achieved. Based on these issues, the objective of this study was to develop service standards for Katimbang Subdistrict in Biringkanaya District, Makassar City. This study applied descriptive qualitative approach to describe the phenomena occurring naturally and comprehensively in Katimbang Village. Data was collected through observation, interviews, and focus group discussions. The result of this study is a Service Standard Document that includes three types of services: Service Standard for Domisili Certificate, Service Standard for Certificate of Inability, and Service Standard for Business Certificate. These documents can serve as a reference for serving the public. Recommendations for improving service quality in Katimbang Subdistrict include the addition of a suggestion box.